The changing role of the IMF - Vasilov, Vangel (2013)
This paper analyses the role of the "International Monetary Fund" in the global economy, from its creation and its original purpose, up to the present and its revised role. It elaborates the need for its creation, its organizational structure, all members and non-members rights and obligations and the organization's path in implementing reforms In order to cope with the changing environment. In the end, analysis and comparison is made between 3 cases in which the "Fund" took action in. Analysis on the influence, policies and changes on macroeconomic level, which the organization managed to achieve and "mend" the overall situation.